Tree-ring footprints of drought variability in last ∼300 years over Kumaun Himalaya, India and its relationship with crop productivity. (1st June 2015) - Yadav, Ram R.; Misra, Krishna G.; Yadava, Akhilesh K.; Kotlia, Bahadur S.; Misra, Sandhya
Abstract: We reconstructed Standardized Precipitation Index (SPI), a metric of drought, using tree-ring width chronologies of Himalayan cedar ( Cedrus deodara (Roxb.) G. Don) prepared from two ecologically homogeneous settings in the Kumaun Himalaya, India. The reconstruction employing first principal component of the two site chronologies in linear regression model helped in extending 7-month SPI of May (SPI7-May) back to 1720 CE. The calibration model capturing 60% of variance in the observed SPI series (1902–1967) is the strongest so far from the Indian region. On achieving such a robust tree-ring calibration we are of the opinion that SPI should provide a better option to develop long-term drought records for the data scarce Himalayan region. The SPI reconstruction revealed high year-to-year variability with 1816 (SPI −1.92) and 1737 (SPI +2.33) the driest and the wettest years respectively. The five year mean of reconstructed SPI revealed multiyear droughts in 1920–1924, 1782–1786, 1812–1816, 1744–1748, 1964–1968 and pluvial phases in 1911–1915, 1723–1727, 1788–1792, 1758–1762 and 1733–1737. The SPI7-May was found to be significantly correlated with wheat-barley productivity data of Almora in Kumaun, close to our tree ring sites (r = 0.60, two-tailed p < 0.0001). However, we observed that the wheat-barley productivity data, to some extent, were better correlated with 7-month SPI of April (SPI7-April) (r = 0.69, two-tailed p < 0.0001). The difference in relationship of wheat-barley productivity and SPI of above two periods is largely due to the prevailing crop phenology in the region. The wheat and barley crops sown in October–November are usually harvested in May when the Himalayan cedar trees are in active vegetation phase of seasonal growth in Almora region. We observed strong and significant correlation in SPI7-May and SPI7-April (r = 0.75, two-tailed p = 0.0001) underpinning that the tree-ring derived SPI7-May could also be taken as a proxy of wheat-barley production in Almora region. This observation also stands for the past as we noted that most of the droughts recorded in our reconstruction (SPI <1) were associated with rabi crop failures in the Kumaun Himalaya. The findings of this study establish that the SPI7-May developed from tree rings should serve as an important base line data to quantify the impact of droughts on forest as well as rabi crop productivity in hilly terrains of the Kumaun Himalaya in long-term perspective. Highlights: Standardized Precipitation Index (SPI) developed from Himalayan cedar chronologies. Reconstructed SPI displayed high year-to-year variability. SPI significantly correlated with wheat and barley productivity in rainfed system. Historical droughts recorded in reconstruction associated with rabi crop failures.